THE ROLE OF SOCIAL SCIENCES IN CHARACTER EDUCATION BASED ON PANCASILA STUDENT PROFILES - Marsini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to analyze the role of social science in character education based on the Pancasila Student Profile (Profil Pelajar Pancasila). In accordance with the demands of the times and developments in people's lives including changes in the education curriculum, social studies learning must be returned in accordance with its latest conceptual framework which emphasizes interdisciplinary and transdisciplinary, with contextual and transformative, active and participatory learning in the perspective of social values. using descriptive qualitative research methods with data collection carried out by literature study, observation, document analysis, and interviews. The results of the study show that in the social studies learning process, efforts should be made to include Pancasila values which are also currently in the context of the Merdeka curriculum already summarized in the Pancasila Student Profile which consists of dimensions of faith and piety to God Almighty and noble character, Global diversity, mutual cooperation, independent, creative, and able to reason critically. This is useful for the formation of student personality as a provision for living in society both as citizens and global citizens.